Proceedings of the 2021 Conference on Empirical Methods in Natural Language Processing 2021
DOI: 10.18653/v1/2021.emnlp-main.42
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Language-Dependent Ethnic Bias in BERT

Abstract: BERT and other large-scale language models (LMs) contain gender and racial bias. They also exhibit other dimensions of social bias, most of which have not been studied in depth, and some of which vary depending on the language. In this paper, we study ethnic bias and how it varies across languages by analyzing and mitigating ethnic bias in monolingual BERT for English, German, Spanish, Korean, Turkish, and Chinese. To observe and quantify ethnic bias, we develop a novel metric called Categorical Bias score. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 26 publications
(46 reference statements)
0
21
0
Order By: Relevance
“…It is important to note the difference between our work and other work that has been carried out on ethnic bias in NLP models, e.g., Ahn and Oh (2021) and Nadeem et al (2021). The concern of these studies is stereotypes that are expressed about members of ethnic minorities.…”
Section: Discussionmentioning
confidence: 80%
“…It is important to note the difference between our work and other work that has been carried out on ethnic bias in NLP models, e.g., Ahn and Oh (2021) and Nadeem et al (2021). The concern of these studies is stereotypes that are expressed about members of ethnic minorities.…”
Section: Discussionmentioning
confidence: 80%
“…In prior work on MLMs, social biases for languages other than English have rarely been investigated. Ahn and Oh (2021) investigated ethnic bias in monolingual MLM in six languages by extending the templates to other languages using machine translation. The biases of MLMs have been evaluated using templates for English and Chinese (Liang et al, 2020) and for English and German (Bartl et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Similar to any AI model, existing inequalities in big models may compound historical discrimination [1103], by producing unfair results, information cocoon, and disproportionately negative consequences to minorities [1104,1105,1106]. Since big models may affect downstream applications, understanding how biases produce in big models and their harms has attracted attention recently [1107,20,1108,1109,1110,1111,1112,1113].…”
Section: Fairnessmentioning
confidence: 99%
“…However, even if the social bias is eliminated at the word level, the sentence-level bias can still exist due to the imbalanced combination of words. Recently, there have been several studies on how to measure sentence-level bias [1136,1137,1109]. Moreover, Xu et al [1111] showed that detoxification techniques, which are useful in language models, may hurt equity.…”
Section: Fairnessmentioning
confidence: 99%